The Role of the Value Proposition Canvas in Supporting Business Sustainability at Rakamin Academy - Putri, Mayangsari Alifah; Nur Hidayati, Utami; Dianka, Olga Koswanurfan (Communicare : Journal of Communication Studies, 2025)
The phenomenon of mass layoffs and the shutdown of numerous startups in recent years reflects the fragility of startup business models. This study aims to analyze the elements of the Value Proposition Canvas and to identify how the value propositions designed support the resilience and sustainability of Rakamin Academy's business. The research adopts a qualitative phenomenological approach through semi-structured interviews and document analysis. The findings reveal that Rakamin is among the most affordable bootcamps, offering professional mentors in their respective fields and relevant materials for both upskilling and career transitions. Rakamin offers programs including boot camps, virtual internships, and career guidance. A strong alignment was found between customer needs and the value propositions offered, as reflected in three types of fit: problem-solution fit, product-market fit, and business model fit. The study also identifies captured value, missed value, and opportunities for new value creation, such as long-term career support and strategic partnerships, that are sufficiently well developed and contribute to Rakamin's positioning as a sustainable digital talent platform.